Liveworksheets en la enseñanza-aprendizaje de matemática, bloque curricular medida, en séptimo grado de la Unidad Educativa Particular "San Gerardo" - Patiño Abad, Andrea Maribel (2022)
The present investigation called live worksheets in the teaching-learning of mathematics, a measured curricular block, in the seventh grade of the "San Gerardo" Private Educational Unit is important because technological tools have greatly influenced our mathematics classrooms by allowing dynamic, active and innovative learning. Its general objective is: To incorporate live worksheets in the teaching-learning of mathematics curricular block measured in the seventh grade of the "San Gerardo" Private Educational Unit. Likewise, for the fulfilment of the general objective, the following specific objectives were proposed: Describe the characteristics of live worksheets and their contribution to the teaching-learning process of mathematics curricular block measure. To identify the use of live worksheets in the teaching-learning of mathematics curricular block measured in the seventh grade of the "San Gerardo" Private Educational Unit. Design interactive activities in Live worksheets for the teaching-learning of the mathematics curricular block measured in the seventh grade of the "San Gerardo" Private Educational Unit. The study was proposed with a qualitative-quantitative mixed methodological approach and the type of research is correlational, with methods: observational, synthetic analytical, inductive, deductive, hermeneutical, statistical, descriptive; the techniques used interview, survey; instruments: structured base interview, written questionnaire; As a result, it was found that the teacher is unaware of the use, creation of live worksheets and the benefit it provides by incorporating this tool into the teaching-learning process of measurement, which generates students' disinterest in their learning. 54 students and one teacher participated in the research work. It is concluded that using live worksheets in the teaching-learning process of Measurement is essential to link students with technology and build meaningful learning. Keywords: live worksheets, teaching-learning, Technological tools